2001
DOI: 10.1046/j.1365-3091.2001.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Storm deposits and storm‐generated coarse carbonate breccias on a pelagic outer shelf (South‐East Basin, France)

Abstract: Uppermost Jurassic limestones of the South‐East Basin (France) are organized into four facies associations that were deposited in four distinct zones: (1) peritidal lagoonal limestones; (2) bioclastic and reefal limestones; (3) pelagic lime mudstones; (4) lime mudstones/calcarenites/coarse breccias. Calcarenite deposits of zone 4 exhibit sedimentary structures that are diagnostic of deposition under wave‐induced combined flow. In subzone 4a, both vertical and lateral transitions from lime mudstone/calcarenite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…The scourand-fill structures observed at the bases must have been created by storm-induced bottom currents or combined flows winnowing the sea floor (cf. Seguret et al, 2001). The geopetal infillings in fossils suggest rapid burial during storm events (Flügel, 2004, p.178).…”
Section: Discussionmentioning
confidence: 99%
“…The scourand-fill structures observed at the bases must have been created by storm-induced bottom currents or combined flows winnowing the sea floor (cf. Seguret et al, 2001). The geopetal infillings in fossils suggest rapid burial during storm events (Flügel, 2004, p.178).…”
Section: Discussionmentioning
confidence: 99%
“…The process of cyclic wave loading invoked by Seguret et al (2001) may be partly invoked to explain some of the features observed in the Hoogland breccias. Cyclic wave loading of the sea-floor entails the periodic displacement of sub-surface sediments (Suhayda, 1977), such that slowly applied shear stresses strain the strata and liquefy the muds as pore pressures progressively increase (Clukey et al 1985).…”
Section: E Matrix Supported Brecciasmentioning
confidence: 99%
“…As the storm swell dissipated, the continued application of layer-parallel shear stresses macerated any stratigraphy not already cemented to form the platy, intraclastic matrix. The newly produced slurry of platy intraclasts and larger rafts would have locked into place once the layer-parallel shear stresses decreased below the Bingham threshold for deformation (Seguret et al 2001). A further decrease in current velocities and shear stresses resulted in the deposition of hummocky crossstratified beds, overlain by wave-oscillation ripples observed at the tops of brecciated intervals.…”
Section: E Matrix Supported Brecciasmentioning
confidence: 99%
“…(FERRY et al, 2015). The finding of HCS-like features in some beds has been at the origin of a recent controversy (BOUCHET-TE et al, 2001;SEGURET et al, 2001) about the mechanisms of emplacement of the breccias and therefore the actual depth of the basin (see discussion in FERRY et al, 2015). Fig.…”
Section: Uppermost Jurassic To Berriasian Breccias In the Central Vocmentioning
confidence: 99%